Proposing a simple, low-cost experiment to simulate water absorption and transport in young common Bean plants (Phaseolus vulgaris L.) (Research, Society and Development, 2021)
The growth of plants, their development and functioning within their habitat is studied by the area of ​​Biology called          Plant Physiology. In high school, this area is seen by students as complex and tedious, as it has many processes and             terms that must be very well contextualized. In order to overcome such problems, the present work has as main        objective to facilitate and instigate students' learning in the discipline of Biology, in High School, more precisely   within Plant Physiology, regarding the topic of water absorption and transport in angiosperms by means of of a simple        and low-cost experiment using young common Bean plants (Phaseolus vulgaris L.) as a model. Thus, the practical           activity in question allows to promote a greater interest of the students, facilitating the contextualization besides    allowing the work of the scientific experimentation, being a task of great impact of the teaching process.